2021
DOI: 10.3390/cancers13061315
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Quality of Life and Hearing Following Radiosurgery for Vestibular Schwannoma

Abstract: Background: Most existing publications on quality of life (QoL) following stereotactic radiosurgery (SRS) for vestibular schwannomas (VS) gather information retrospectively by conducting surveys several years after treatment. The purpose of this study is therefore to provide longitudinal QoL data and assess how changes in hearing impact QoL. Methods: Patients completed the 12-item short-form (SF-12) health survey prior to treatment and at every follow-up visit. One hundred and seventy-five patients who had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…[5][6][7] Longitudinal studies lack long-term follow-up (2-3 years), 14,15 do not use a disease-specific questionnaire, [16][17][18] or focus only on 1 treatment modality. [16][17][18] This study aims to find the long-term longitudinal QoL outcomes and evaluates decisional regret in patients with VS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Longitudinal studies lack long-term follow-up (2-3 years), 14,15 do not use a disease-specific questionnaire, [16][17][18] or focus only on 1 treatment modality. [16][17][18] This study aims to find the long-term longitudinal QoL outcomes and evaluates decisional regret in patients with VS.…”
mentioning
confidence: 99%
“…Previous studies on long-term QoL in patients with VS were cross-sectional in design and showed no clinically relevant differences between treatment modalities. [5][6][7] Longitudinal studies lack long-term follow-up (2-3 years), 14,15 do not use a disease-specific questionnaire, [16][17][18] or focus only on 1 treatment modality. [16][17][18] This study aims to find the long-term longitudinal QoL outcomes and evaluates decisional regret in patients with VS.…”
mentioning
confidence: 99%
“…The main outcome of this study was HRQoL, which was calculated using responses to the 12‐Item Short‐Form Survey (SF‐12), which has been used in previous studies to determine the HRQoL in patients with hearing loss. 16 , 17 , 18 Patients completed the SF‐12 on the day of their visit to measure their HRQoL at the time of their symptoms. The SF‐12 is an abbreviated version of the 36‐Item Short‐Form Survey.…”
Section: Methodsmentioning
confidence: 99%
“…It has been hypothesized that microsurgery may confer an advantage with regard to patient’s MH, relating to the psychological benefit of “cure” from tumor removal ( 17 ). In general, however, QoL data in VS treatment differentiating between PH and MH is scarce ( 14 , 17 , 18 , 22 ).…”
Section: Introductionmentioning
confidence: 99%